2012
DOI: 10.1212/wnl.0b013e3182759766
|View full text |Cite
|
Sign up to set email alerts
|

Acute EEG findings in children with febrile status epilepticus

Abstract: Objective: The FEBSTAT (Consequences of Prolonged Febrile Seizures) study is prospectively addressing the relationships among serial EEG, MRI, and clinical follow-up in a cohort of children followed from the time of presentation with febrile status epilepticus (FSE). Methods:We recruited 199 children with FSE within 72 hours of presentation. Children underwent a detailed history, physical examination, MRI, and EEG within 72 hours. All EEGs were read by 2 teams and then conferenced. Associations with abnormal E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 26 publications
4
49
0
Order By: Relevance
“…A limitation of the prior studies is that they lacked imaging data to correlate with the EEG findings. In the FEBSTAT study, both EEG and MRI were performed in the postictal state [76,117]. Overt epileptiform abnormalities were uncommon, however focal slowing or attenuation or both (usually maximal over the temporal area) were present in over 30 % of the cases.…”
Section: Eeg As a Potential Predictive Marker For Tle That Follows Fsementioning
confidence: 99%
“…A limitation of the prior studies is that they lacked imaging data to correlate with the EEG findings. In the FEBSTAT study, both EEG and MRI were performed in the postictal state [76,117]. Overt epileptiform abnormalities were uncommon, however focal slowing or attenuation or both (usually maximal over the temporal area) were present in over 30 % of the cases.…”
Section: Eeg As a Potential Predictive Marker For Tle That Follows Fsementioning
confidence: 99%
“…In one study, EEG performed within the 72 hours following febrile status epilepticus revealed the presence of focal abnormalities (90 out of 199 EEGs), and rarely focal spikes (13 EEGs). These focal abnormalities were significantly more frequent in focal seizures, when MRI evidenced hippocampal T2 signal abnormality and when the fever was not very high [25]. In another study on 119 children presenting with febrile seizures, EEG abnormalities (EEG performed between 7 and 21 days later) were seen in 26 cases (21.8%) and 9 children (7.6%) developed epilepsy later on.…”
Section: Neurological Disordersmentioning
confidence: 93%
“…They concern 2-5% of affected children, mostly aged between 6 months and 5 years [Stafstrom, 2002]. A recent multicentric prospective study evaluated long-term consequences of febrile status epilepticus on 200 children and showed MRI (hippocampal and temporal lobe) and EEG abnormalities (1/3 presented focal temporal slowing) [Nordli et al, 2012] within the first 72 h, while CSF analysis was unremarkable [Frank et al, 2012].…”
Section: Febrile Seizuresmentioning
confidence: 99%